Pengaruh Live Streaming, Brand Trust, dan Online Customer Reviews Terhadap Minat Beli di Platform Tiktok Shop - Lailil Mas’Uda; Misti Hariasih; Sumartik Sumartik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Advances in digital technology have changed consumer behavior from conventional shopping patterns to online shopping, including the increased use of Tiktok Shop as a transaction platform. Tiktok Shop offers live streaming features, brand trust, and online customer reviews to increase consumer confidence and interest in making purchases. This study aims to analyse the extent to which live streaming, brand trust, and online customer revuews influence purchasing interest on Tiktpk Shop. The research approach uses quantitave methods with primary data collected through questionnaires and secondary data from various supporting references. The number of respondents was determined using the Lemeshow formula, resulting in 96 people, which was then rounded up to 100 respondents. Data analysis involved multiple linier regression, validity testing, reliability testing, normality testing, autocorrelation testing, ,ulticolinearity tesying, heteroscedasticity testing, t-testing, and determination testing. The results showed that the three variables of live streaming, brand trust, and online customer reviews had a significant influence on the purchasing interest of Tiktok Shop users.